New proposals for the detection of the Earth's gravitomagnetic field in space-based and laboratory-based experiments - Iorio, L (2003)
In this contribution we present two new proposals for measuring the general relativistic gravitomagnetic component of the gravitational field of the Earth. One proposal consists of the measurement of the difference of the rates of the perigee $ψ$ from the analysis of the laser--ranged data of two identical Earth'artificial satellites placed in equal orbits with supplementary inclinations. In this way the impact of the aliasing classical secular precessions due to the even zonal harmonics of the geopotential would be canceled out, although the non--gravitational perturbations, to which the perigees of LAGEOS--type satellites are particularly sensitive, should be a limiting factor in the obtainable accuracy. With a suitable choice of the inclinations of the orbital planes it would be possible to reduce the periods of such insidious perturbations so to use not too long observational time spans. However, the use of a pair of drag--free satellites would greatly reduce this problem, provided that the time span of the data analysis does not excess the lifetime of the drag--free apparatus. In the other proposal the difference of the rotational periods of two counter-revolving particles placed on a friction-free plane in a vacuum chamber at the South Pole should be measured in order to extract the relativistic gravitomagnetic signal. Among other very challenging practical implications, the Earth's angular velocity $ω_{\oplus}$ should be known at a $10^{-15}$ rad s$^{-1}$ level from VLBI and the friction force of the plane should be less than $2× 10^{-9}$ dyne.